Disk-like micelles with cylindrical pores from amphiphilic polypeptide block copolymers. Issue 16 (24th March 2016) - Lin, Xue; He, Xiaohua; Hu, Chaoqun; Chen, Yuxiang; Mai, Yiyong; Lin, Shaoliang
Abstract : An unprecedented 2-dimensional disk-like micelle with cylindrical pores was achieved by self-assembly of amphiphilic block copolypeptides PEG- b -PBLG with an α-helical conformation of PBLG blocks. Abstract : An unprecedented two-dimensional (2D) disk-like micelle with cylindrical pores was achieved for the first time by self-assembly of the amphiphilic block copolypeptide poly(ethylene glycol)- block -poly(γ-benzyl-l -glutamate) (PEG- b -PBLG) in solution. The aggregate structures were fully characterized by TEM, SEM, 1 H NMR, AFM and CD. The research results showed that the α-helical conformation of PBLG blocks plays a key role in the formation process of a disk-like morphology. By tuning the ratio between the hydrophilic block and hydrophobic block in PEG- b -PBLG copolymers, various aggregate structures including micelles, disk-like micelles, vesicles and large vesicles can be achieved. The research results are helpful to expand the self-assembly fields and can provide more nanostructural materials.